Suitable Media for Cultivation of Cordyceps militaris - อวรัญ, สุภาพร (Journal of Vocational Education in Agriculture, 2020)
The objective of this research was to study culture media and sterile method for fruiting body formation of Cordyceps militaris. C. militaris cultured on 9 formulas of culture medium using completely randomize design (CRD) with 10 replications. The results showed that the culture medium formula 2, 7, 8 and 9 gave the highest fruiting body dry weight was not significantly different and medium formula 9 (jasmine brown rice mixed with medium #3) gave the highest fruiting body dry weight at 3.9 g. The fruiting body dry weight formula 8 (jasmine brown rice mixed with medium #2), formula 2 (riceberry brown rice mixed with medium #2), formula 7 (jasmine brown rice mixed with medium #1) and formula 3 (riceberry brown rice mixed with medium # 3) and gave fruiting body dry weight at 3.8, 3.8, 3.6 and 3.5 g, respectively. The comparison between 2 sterile method, found that using of 100 mL of hydrogen peroxide (H2O2) in culture medium and steamed at 100°C for 3 hr. gave a better result than autoclave for 45 min.